TRANSCULTURALITY AND BEYOND: THE CASE OF “LITTLE BLUE AND LITTLE YELLOW” - Werner Delanoy (Italiano LinguaDue)
In this article, transculturality will be given due credit for drawing attention to changing conditions for culture formation in a globalized modernity. However, a less optimistic picture will be drawn by highlighting the shortcomings of early positions and by suggesting alternative concepts going beyond the confines of this approach. As regards alternative positions, references will be made to cosmopolitan, global citizenship-related, posthumanist and ecocritical perspectives. Moreover, the question will be raised whether transculturality as suggested in the 1990s still is a timely model for cultural learning in the current decade. In conceptual debates ideas often remain abstract and divorced from concrete realities. Therefore, the following reflections will be linked to Leo Lionni’s Little Blue and Little Yellow, a book for very young children, first published in 1959. The book vividly shows how a certain notion of transculturality works, and it can illustrate in simple terms a highly abstract concept.